Current and Emerging Treatments for Postsurgical Cleft Lip Scarring: Effectiveness and Mechanisms - Papathanasiou, E. (J Dent Res, 2017)
Cleft lip with or without cleft palate is the most common congenital malformation of the head and the third-most common birth defect. Surgical repair of the lip is the only treatment and is usually performed during the first year of life. Hypertrophic scar (HTS) formation is a frequent postoperative complication that impairs soft tissue form, function, or movement. Multiple lip revision operations are often required throughout childhood, attempting to optimize aesthetics and function. The mechanisms guiding HTS formation are multifactorial and complex. HTS is the result of dysregulated wound healing, where excessive collagen and extracellular matrix proteins are deposited within the wound area, resulting in persistent inflammation and resultant fibrosis. Many studies support the contribution of dysregulated, exaggerated inflammation in scar formation. Fibrosis and scarring result from chronic inflammation that interrupts tissue remodeling in normal wound healing. Failure of active resolution of inflammation pathways has been implicated. The management of HTS has been challenging for clinicians, since current therapies are minimally effective. Emerging evidence that specialized proresolving mediators of inflammation accelerate wound healing by preventing chronic inflammation and allowing natural uninterrupted tissue remodeling suggests new therapeutic opportunities in the prevention and management of HTS.